2015
DOI: 10.1007/s10257-015-0287-2
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of users’ intention to adopt m-commerce: an empirical analysis

Abstract: The fast-growing penetration of mobile devices and recent advances in mobile technologies have led to the development of increasingly sophisticated services such as m-shopping for goods or services and m-payment. However, although the number of mobile subscribers is increasing, levels of actual m-commerce activities in many cases remain low. Determining what influences users' intention to use m-commerce is therefore of growing importance. The purpose of this study was to investigate possible factors. To this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
88
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(103 citation statements)
references
References 59 publications
7
88
0
8
Order By: Relevance
“…Kim et al (2010) found a significant positive relationship between perceived usefulness and intention to use mobile payment. A similar relationship between the two constructs has been empirically validated in many studies in mobile payment (Busu et al 2018;Kalinic & Marinkovic 2016;Mun et al 2017;Pham & Ho 2015). This leads to the following hypothesis: H1 There is a significant relationship between perceived usefulness and intention to use QR mobile payment.…”
Section: Perceived Usefulnesssupporting
confidence: 55%
“…Kim et al (2010) found a significant positive relationship between perceived usefulness and intention to use mobile payment. A similar relationship between the two constructs has been empirically validated in many studies in mobile payment (Busu et al 2018;Kalinic & Marinkovic 2016;Mun et al 2017;Pham & Ho 2015). This leads to the following hypothesis: H1 There is a significant relationship between perceived usefulness and intention to use QR mobile payment.…”
Section: Perceived Usefulnesssupporting
confidence: 55%
“…Similar to social networking, the mobile payment becomes intertwined in consumers’ lives because of its mobility feature. Growing research has shown a positive correlation between mobility and perceived usefulness in studies of adoption of m‐commerce (e.g., Kalinic & Marinkovic, ). The discussion of the three technological characteristics leads to the following predictions:…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…This may provide an opportunity for marketers to treat their key customers in an exclusive and individualized manner and build enduring relationships with them. Additionally, prior researches (Kalinic & Marinkovic, 2016;Carroll, Barnes, & Scornavacca, 2005) also supported that consumers are more receptive and positive to those advertising messages which are according to their individualized needs. Consequently, it is anticipated that:…”
Section: Personalization and Consumer Attitudementioning
confidence: 99%
“…The element of personalization performs a very important role is shaping consumers positive perception towards mobile advertising (Feng et al, 2016;Oztas, 2015) in that a mobile device is not generally used by anyone other than its owner. Therefore, consumers look forward to highly customized offerings on their cell phones (Kalinic & Marinkovic, 2016;Bauer, Reichardt, Barnes, & Neumann, 2005). Marketers and practitioners may utilize customers' history and feedback as tools to gather information about their preferred choices and tailor their offerings accordingly (Morosan, Morosan, DeFranco, & DeFranco, 2016).…”
Section: Personalization and Consumer Attitudementioning
confidence: 99%